Nickel removal characteristics of an immobilized macro fungus: equilibrium, kinetic and mechanism analysis of the biosorption - Akar, Tamer; Celik, Sema; Ari, Asli Gorgulu; Akar, Sibel Tunali (WILEY-BLACKWELL, 2013)
BACKGROUND: An immobilized new biosorbent was prepared from macro fungi Lactarius salmonicolor for the effective removal of nickel ions from aqueous media. Operating conditions were optimized as functions of initial pH, agitation time, sorbent amount and dynamic flow rate. Immobilization and biosorption mechanism were examined and the developed biosorbent was tested for the removal of nickel ions from real wastewater. RESULTS: Biosorption performance of the biomass continuously increased in the pH range 2.08.0. The coverage of the biosorbent surface by silica gel resulted in a significant increase in biosorption yield of nickel ions. The highest nickel loading capacity was obtained as 114.44 mg g1 using a relatively small amount of immobilized biosorbent. Biosorption equilibrium time was recorded as 5 min. Experimental data were analyzed by different isotherm and kinetic models. Infrared spectroscopy, scanning electron microscopy and X-ray energy dispersive analysis confirmed the process. The sorbent exhibited relatively good recovery potential in dynamic flow mode studies. Biosorption capacity of immobilized biosorbent was noted as 14.90 mg g1 in real wastewater. CONCLUSION: Silica gel immobilized biomass of L. salmonicolor is to be a low cost and potential biosorbent with high biosorption capacity for the removal of contaminating nickel from aqueous media. (c) 2012 Society of Chemical Industry
Keywords: biosorption; nickel; immobilized biosorbent; isotherms; kinetics; mechanism; AQUEOUS-SOLUTION; HYBRID BIOSORBENT; WASTE BIOMASS; PB(II) IONS; LEAD II; ADSORPTION; SORPTION; NI(II); CU(II); DYE; Biotechnology & Applied Microbiology; Chemistry; Engineering